Histopathological Observations on Liver and Gills of Clarias gariepinus Juveniles Treated with Some Prophylactics - Jeremiah Olanipekun Jimoh; Bayode Paul Omobepade; Ademola Michael Akinsorotan; John Bunmi Olasunkanmi; Tolulope Omolayo Ariyomo; Victoria Oluwabunmi Fatoyinbo (Department of Aquaculture, 2023)
This study investigated histopathological changes on the liver and gills of C. gariepinus juveniles treated intermittently with different concentrations of prophylactics. Potassium permanganate (T2), Hydrogen peroxide (T3) and Formalin (T4) were used as prophylactics and administered to 15 fish each at concentrations of 2 ppm, 150 ppm, and 100 ppm respectively. The treatments which were in three replicates each with a control set up (T1) were repeated biweekly for 10 weeks. The histomacrographs of the liver and the gills show that there were no visible alterations on the structures of the tissues of fish in the control experiment (T1). However, major histopathological observations for the fish in T2, T3, and T4 were severe degeneration in the gill structure, fusion of the gill rakers, slight changes in the hepatocytes, diffuse vacuolation of hepatocytes. Among the used chemicals, potassium permanganate appeared to have the least negative effects on the tissues and it is therefore recommended at 2 ppm for prophylactic treatment of fish against diseases.